DINAMIKA KIPRAH POLITIK HARY TANOESOEDIBJO DAN PARTAI PERSATUAN INDONESIA (PERINDO) DALAM DEMOKRASI INDONESIA TAHUN 2013-2019 - Hanifa Maylasari; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2019)
Political ideas of political process based on the dynamics of one's gait in politics. A dynamic political process is experienced by a political figure in a certain period of time. The container used as a medium for delivering ideas to political goal is a political party. Ideology as the basic foundation of the movement of political parties is a core part of ideas and that are born of political figures in them. The Chairperson has a considerable contribution in each party's decision-making process, and can be said as a media to legitimate the community in an effort to obtain the most votes for political parties in the General Election. This research focuses on the dynamics political movements of Hary Tanoesoedibjo and Perindo Party in Democracy year 2013-2019.The research method used is a qualitative type of biography by conducting in-depth interviews to find out the history of HT especially in the political field. Case studies and literature studies on the biography of HT are also used as data sharpening and comparison with the results of interviews. Research data is using purposive sampling, namely by directly interviewing the main informants, namely Hary Tanoesoedibjo and other secondary informants supporting the HT trust figures in the political field as well as several other informants involved in his life process. The researcher also made a direct observation of the Perindo Party political campaign process that HT did in Central Java. The system of identifying data analysis results based on time after time biography of political figures.The results of this study indicate that HT political ideas consists of three things, namely political economy, social politics, and cultural politics. This was obtained by HT, because of his background as a businessman who focused on improving the lower class economy and reducing poverty. In accordance with Aristotle's Theory of Political Thought regarding human political personality, and zoon politicon that HT wants to fulfill its ideals as a political being.Keywords: Political Thought, Political Parties, and Politics of Identity.